SHANK3 variant as a cause of nonsyndromal autism in an 11-year-old boy and a review of published literature. Issue 4 (October 2018) - Kanani, Farah; Study, DDD; Balasubramanian, Meena
Abstract : Autism spectrum disorder (ASD) encompasses a spectrum of pervasive neuropsychiatric disorders characterized by deficits in social interaction, communication, unusual and repetitive behaviours. The aetiology of ASD is believed to involve complex interactions between genetic and environmental factors; it can be further classified as syndromic or nonsyndromic, according to whether it is the primary diagnosis or secondary to an existing condition where both common and rare genetic variants contribute to the development of ASD or are clearly causal. The prevalence of ASD in children is increasing with higher rates of diagnosis and an estimated one in 100 affected in the UK. Given that heritability is a major contributing factor, we aim to discuss research findings to-date in the context of a high-risk autism candidate gene, SHANK3 (SH3 and multiple ankyrin repeat domain 3), with its loss resulting in synaptic function disruption. We present a 10-year-old patient with a pathogenic de novo heterozygous c.1231delC, p.Arg411Val frameshift variant in SHANK3 . He presented with severe autism, attention deficit hyperactivity disorder and pathological demand avoidance, on a background of developmental impairment and language regression. The number of genes associated with autism is ever increasing. It is a heterogeneous group of disorders with no single gene conferring pathogenesis in the majority of cases. Genetic abnormalities can be detected in ~15% of ASD and these range from copy number variants in 16p11.2 and 15q13.2q13.3 to several well-known genetic disorders including tuberous sclerosis and fragile X syndrome. Further, high confidence autism genes include but are not limited to NRXN, NLGN3, NLGN4, SHANK2 and SHANK3 .